Jupoata (Coleoptera, Cerambycidae, Cerambycinae): nova espécie da Costa Rica e chave para identificação das espécies - Durán, José Rafael Esteban; Martins, Ubirajara R. (Papéis Avulsos de Zoologia, 2012)
Jupoata (Coleoptera, Cerambycidae, Cerambycinae): new species from Costa Rica and key to the identification of the species. Jupoata brenesi from Costa Rica is described, illustrated and include in a key to the species of the genus.